Significant Upregulation of HERV-K (HML-2) Transcription Levels in Human Lung Cancer and Cancer Cells - Yang, Caiqin; Guo, Xin; Li, Jianjie; Han, Jingwan; Jia, Lei; Wen, Hong-Ling; Sun, Chengxi; Wang, Xiaolin; Zhang, Bohan; Li, Jingyun; Chi, Yujia; An, Tongtong; et al. (Frontiers in Microbiology, 2022)
Lung cancer is the second most common cancer worldwide and the leading cause of cancer death in the world. Therefore, there is an urgent need to develop new and effective biomarkers for diagnosis and treatment. Under this circumstance, human endogenous retroviruses (HERVs) were recently introduced as novel biomarkers for cancer diagnosis. This study focused on the correlation between lung cancer and HERV-K (HML-2) transcription levels. At the cellular level, different types of lung cancer cells and human normal lung epithelial cells were used to analyze the transcription levels of the HERV-K (HML-2) gag, pol and env genes by RT–qPCR. At the level of lung cancer patients, blood samples with background information from 734 lung cancer patients and 96 healthy persons were collected to analyze the transcription levels of HERV-K (HML-2) gag, pol and env genes. The results showed that the transcriptional levels of the HERV-K (HML-2) gag, pol and env genes in lung cancer cells and lung cancer patient blood samples were significantly higher than those in the healthy controls, which was also verified by RNAScope ISH technology. In addition, we also found that there was a correlation between the abnormal transcription levels of HERV-K (HML-2) genes in lung cancer patients and the clinicopathological parameters of lung cancer. We also identified the distribution locations of the gag, pol and env primer sequences on each chromosome and analyzed the function of these loci. In conclusion, HERV-K (HML-2) genes may be a potential biomarker for the diagnosis of lung cancer.